2001
DOI: 10.1149/1.1401084
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene chloride)-Based Carbon as an Electrode Material for High Power Capacitors with an Aqueous Electrolyte

Abstract: The specific capacitance (F/g) of a poly(vinylidene chloride) (PVDC)-based electric double-layer capacitor (EDLC) carbon electrode prepared by heat-treatment at only 700°C shows a capacitance as high as 64 F/g at 1 mA output current density, although it shows a specific surface area of only 700 m2/g, smaller than those of other conventional activated carbon fibers and activated carbons. To elucidate the relationship between the specific capacitance and the pore structure for PVDC-based carbons, from an EDLC pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 10 publications
3
41
1
Order By: Relevance
“…The monolith density decreases with removal of oxygen groups and development of porosity [42]. The density found for the three monoliths is higher than that reported for other carbon monoliths, with densities usually below 0.6 g cm -3 [2,20,21,24,26,27,[29][30][31][32], and also higher than the density of pellets obtained from PVDC-based carbon powders [43,44].…”
Section: Physical Characterizationmentioning
confidence: 75%
See 1 more Smart Citation
“…The monolith density decreases with removal of oxygen groups and development of porosity [42]. The density found for the three monoliths is higher than that reported for other carbon monoliths, with densities usually below 0.6 g cm -3 [2,20,21,24,26,27,[29][30][31][32], and also higher than the density of pellets obtained from PVDC-based carbon powders [43,44].…”
Section: Physical Characterizationmentioning
confidence: 75%
“…In the literature, sizes for dehydrated and hydrated sulfate ions, of ca. 0.5 nm and 0.6-1 nm, respectively, have been reported [30,43,[45][46][47]. The proton size is still uncertain and the size seems to depend on the pH and counter ion [48][49][50].…”
Section: Physical Characterizationmentioning
confidence: 97%
“…[13] However, in some other experiments, it has been found that there is no such linear relationship. [14,15] There are also some experiments showing that there is a linear relationship between C and micropore volume. [16,17] The effects of pore size and d on C are also not clear.…”
mentioning
confidence: 99%
“…3a), we can find that the capacitance of the positive electrode is relatively much smaller than that of the negative electrode, which can be ascribed to the high diffusion resistance of the large hydrated anion [SO 4 ·(H 2 O) n ] 2− (n06, 12) [28] into the micropores of AC under the internal electric fields.…”
Section: Resultsmentioning
confidence: 99%